Efficacy of GLP‐1 Receptor Agonist‐Based Therapies on Cardiovascular Events and Cardiometabolic Parameters in Obese Individuals Without Diabetes: A Meta‐Analysis of Randomized Controlled Trials - Yin, Yue; Zhang, Minghan; Cao, Qiuyu; Lin, Lin; Lu, Jieli; Bi, Yufang; Chen, Yuhong (Journal of diabetes, 2025)
ABSTRACT Background The cardioprotective effects of glucagon‐like peptide‐1 receptor agonist (GLP‐1RA)‐based therapies in nondiabetic individuals with overweight or obesity remain underexplored. This meta‐analysis evaluates their impact on cardiovascular events and metabolic parameters in this population. Methods A meta‐analysis was conducted using PubMed, Embase, Cochrane, and Web of Science databases from inception to June 18, 2024. Eligible studies were randomized controlled trials (RCTs) enrolling nondiabetic adults with overweight or obesity. These studies compared GLP‐1RA‐based therapies with placebo and reported cardiovascular events and metabolic parameters. Results A total of 29 RCTs involving 9 GLP‐1RA‐based drugs and 37 348 eligible participants were included. Compared to placebo, GLP‐1RA‐based therapies significantly reduced the risk of total cardiovascular events (relative risk: 0.81, 95% confidence interval [CI]: [0.76, 0.87]), major adverse cardiovascular events (0.80, [0.72, 0.89]), myocardial infarction (0.72, [0.61, 0.85]), and all‐cause mortality (0.81, [0.71, 0.93]). No significant differences were observed in cardiovascular death or stroke. Additionally, GLP‐1RA‐based therapies were associated with significant reductions in some cardiometabolic parameters. Among GLP‐1RA‐based therapies, orfroglipron demonstrated strong benefits in reducing systolic blood pressure (mean difference: −7.10 mmHg, 95% CI: [−11.00, −2.70]). Tirzepatide induced the greatest reduction in body mass index (−6.50 kg/m2, [−7.90, −5.10]) and hemoglobin A1c concentrations (−0.39%, [−0.52, −0.26]). Retatrutide and semaglutide were most effective in improving lipid profiles and reducing C‐reactive protein levels (−1.20 mg/dL, [−1.80, −0.63]), respectively. Conclusions In nondiabetic individuals with overweight or obesity, GLP‐1RA‐based therapies significantly reduce cardiovascular events and improve cardiometabolic parameters. These findings underscore the potential for individualized GLP‐1RA‐based therapies targeting cardiovascular risk factors.